WARM-UP IN FOOTBALL Optimize Performance and Avoid Injuries - Bangsbo, Jens; Skovgaard, Casper (Routledge, 2021)
Every football training session and match should begin with a warm-up in order to improve performance and reduce the risk of injuries. Warm-up in Football provides scientific evidence for the effect of warming-up and describes how performance is closely related to muscle temperature. Furthermore, how the right warm-up prior to a match and at half time does improve the outcome in football. This book provides a basic understanding of the value of warming-up and present a significant number of warm-up programs that can be used whether you are training professional, amateur or youth players. The warm-up programs and exercises are tailored to different training and match situations both on and off the pitch. Highlights from the book include: New inspiring and effective ways of warm-up for training. Warm-up programs before matches. Warm-up programs to improve performance at the start of second half. Warm-up in Football is critical reading to all who have an interest in the coaching and physiology of football.